The Effectiveness of Fluid Physics Practicum Module Based On Wetland Environment to Train Science Process Skills - Zainuddin Zainuddin; Mastuang Mastuang; Misbah Misbah; Melisa Melisa; Fitriana Dewi Ramadhani; Desi Rianti; Ida Rusmawati (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2020)
The purpose of this study was to describe the effectiveness of a wetland environment-based practicum module to train students' science process skills. This research was a research and development study with a 4D model (Define, Design, Develop and Disseminate) with the limitations of this research in the form of product effectiveness only. The product has been validated and the result was 89% categorized as very valid. The subjects of the trial were students of Lambung Mangkurat University Physics Education and the subjects of the distribution stage were Physics Tadris students UIN Antasari. The instrument used in the study was a science process skills assessment sheet, meanwhile the data analysis is done by calculate the n-gain on the value of science process skills and accompanied by the average value of each meeting as supporting data. The results shows that this module was effective in the medium category. It can be conclude that this wetland environment-based practicum module is effective for use in lectures.